Social Attitudes, Environmental Factors, and Laws-Institutions Impacts on School Dropouts: Case Studies in Sumba Island - Yufrinalis, Marianus; Uran, Stefanus Igolois Grenga (Utamax : Journal of Ultimate Research and Trends in Education, 2023)
This research is based on the fact that most children in West Sumba and Central Sumba are forced to drop out of school for various very crucial reasons. The purpose of this study refers to efforts to identify various factors that influence the high dropout rate. The collected data shows that the number of primary school dropouts in West Sumba was 151 students (0.76%) from 18,772 primary school students in the regency. The highest number was in the Lamboya and Tanarighu districts, making up 2.02% and 1.06%, respectively. The percentage is even lower for secondary school dropouts, which is 0.006% of the total of 13,368 junior high school students in West Sumba. The percentage of school dropouts at the primary schools in the Central Sumba Regency is 0.72%. From the collected data, the highest dropout rates are in the districts of Mamboro (1.28%). The percentage of secondary school dropouts in Central Sumba is 2.14%. The highest numbers were in the districts of Umbu Ratu Nggay Barat (3.61%), Katikutana Selatan (2.42%), Katikutana (2.04%), Mamboro (1.70%), and Umbu Ratu Nggay (1.21%). From the information above, the highest dropout rates for primary and secondary schools are in Umbu Ratu Nggay Barat and Katikutana Selatan districts. The main factors causing the high dropout rate in these two districts are Social Attitudes, Environmental Factors, and Laws and Institutions